EXCHANGE RATE ON THE PERFORMANCE OF THE MANUFACTURING SECTOR IN NIGERIA - Helen Walter Mboto; Takon Samuel Manyo; A. Omang Bekom; Stephen Ekpo Nkamare; Asukwo Joseph Ita (International Studies Journal)
The study examined exchange rate on the performance of the manufacturing sector in Nigeria. The specific objectives were to; examine the impact of exchange rate and money supply on the performance of the manufacturing sector in Nigeria. Secondary data was extracted from Central Statistical Bulletin, 2021. Ordinary least square of multiple regression technique was employed to examine the impact of independent on dependent variables. Based on the results, the findings revealed that exchange rate had negative and significant impact on performance of manufacturing sector, while money supply had a positive and significant effect on the performance of the manufacturing sector. The study recommended thatthere is need for local sourcing of raw materials and input through agriculture and technological policy. By so doing, it will lead to expansion of export base which would attract more foreign exchange into the country. Also, the monetary authority should introduce direct policies of regulating price stability in the economy via regulating money supply in order to decelerate the rising inflationary trend in the economy.